Comparison of Nursing Home Hearing Handicap Index with Audiological Findings: A Presbycusis Study - M. H. Nilforoush; A. A. Nasr Esfahani; R. Ishaghi; M. Sepehrnejad (Journal of Aging Research)
Hearing evaluation usually includes hearing threshold assessment, middle ear function, and word recognition tests that lead to an accurate result of peripheral and central auditory system. However, they have some limitations because they cannot fully encompass all aspects of hearing loss problems. Using self-assessment approach, via a questionnaire or telephone survey, is one of the easiest methods to study hearing loss in population. In this research, 60 nursing home residents (27 females and 33 males) ranging from 55 to 85 years with a mean age of were studied via completing self-assessment questionnaire by the elderly cases (NHHI self-version) and the other one was filled by the nursing home personnel (NHHI staff-version). The effects of the hearing loss level on the self- and staff-version scores indicated that there is a significant relationship between self- and staff-version with hearing loss levels () in male and female. Results from this study demonstrate the usefulness of NHHI questionnaire for evaluating hearing handicap of aged people and it may be a useful adjunct in setting up treatment and determining proper care.